The Information and Communication Technologies in the Faculties of Education - Durán Medina, José Francisco; Vega Baeza, Mª Rita (Historia y Comunicación Social, 2014)
This article highlights the importance of a quality initial teacher formation about the Information and Communication Technologies (ICT). Initial training that it should be included as a compulsory subject in the Faculties of Education and also it should be completed with an imperative continuing education for active teachers. This premise is one of the pillars basic to get a quality education a competent education present and future.
Keywords: ICT; Formation; Education.